2014
DOI: 10.1021/ef500993d
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading and Viscosity Reduction of Heavy Oil by Catalytic Ionic Liquid

Abstract: A new class of catalytic ionic liquids, 1-butyl-3-methylimidazolium chloride [BMIM][FeCl4] and its modified version, 1-butyl-3-methylimidazolium tetrachloroferrate [BMIM][FeCl4], were systematically investigated. The modified ionic liquid [BMIM]­[FeCl4] was used to upgrade heavy crude oils. The effects of the reaction temperature and the amount of water on the upgrading of heavy crude oils were studied. The reduction of viscosity by [BMIM]­[FeCl4] is remarkable when the amount of water in the heavy crude oil i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Similarly, TiO 2 has served as a good modifying agent for alumina supporting CoMo, for HDM and HDS [105]. In addition, temperature tolerant ionic liquid-modified catalysts such as imidazolium tetracholoferrate BMIM [FeCl 4 ] when added to heavy crude (at 0.25, 0.5 and 1 % catalyst oil ratio) can achieve remarkable reduction in viscosity (52.2 %), and HDS (20 %) at 70 to 90 °C [106].…”
Section: Modification Of Heterogeneous Catalystsmentioning
confidence: 99%
“…Similarly, TiO 2 has served as a good modifying agent for alumina supporting CoMo, for HDM and HDS [105]. In addition, temperature tolerant ionic liquid-modified catalysts such as imidazolium tetracholoferrate BMIM [FeCl 4 ] when added to heavy crude (at 0.25, 0.5 and 1 % catalyst oil ratio) can achieve remarkable reduction in viscosity (52.2 %), and HDS (20 %) at 70 to 90 °C [106].…”
Section: Modification Of Heterogeneous Catalystsmentioning
confidence: 99%
“…The process was seen to be more efficient viscosity reducer when certain amount of sulfur was present in the oils and the water content in the oil was less than 10%. Further progress on the similar class of ILs, the modified versions of 1-butyl-3methylimidazolium tetrachloroferrate [BMIM] [FeCl 4 ], were prepared by Shaban et al [47]. and studied through physicochemical methods and catalytic activity measurements, with special emphasis on the reaction temperature and the water content in the heavy crude oils.…”
Section: Heavy Oil Dissolution and Viscosity Reductionmentioning
confidence: 99%
“…and studied through physicochemical methods and catalytic activity measurements, with special emphasis on the reaction temperature and the water content in the heavy crude oils. It was found that [BMIM] [FeCl 4 ] family of ILs have the best effect on the heavy crude oil upgradation between 70-90°C temperature and water content less than 8% [47].…”
Section: Heavy Oil Dissolution and Viscosity Reductionmentioning
confidence: 99%
“…Transport of heavy crude oil is probably the most determinant aspect in crude oil profitability, and to alleviate it, several methodologies have been implemented to modify their viscosity: heating, dilution by mixtures with light crude oils or crude oil fractions (condensate, gasoline, kerosene, or naphtha), emulsification of oil in water (o/w), and annular flow core . In Colombia, these methodologies are frequently used in heavy oil wells; however, there are novel advances and technologies that achieve viscosity reduction, such as visbreaking of heavy oils applying microwave radiation, viscosity reduction by aquathermolysis with coordination complexes and the use of catalytic ionic liquids, nanoparticles, and quadripolymers. …”
Section: Introductionmentioning
confidence: 99%